PENGARUH LINGKUNGAN KERJA, IKLIM ORGANISASI DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERTANIAN, PANGAN DAN PERIKANAN KABUPATEN KARANGANYAR - Sutanto, Djoko; Sukorina, Diana; Ramadani, Arifin Awalun (Surakarta Management Journal, 2024)
AbstractThis study investigates the impact of the work environment, organizational climate, and motivation on the productivity of employees at the Karanganyar Regency Agriculture, Food, and Fisheries Service. The subjects of the research were the employees of this service, with a total population of 149 individuals and a sample size of 75. Data was gathered from both primary and secondary sources through methods including surveys, questionnaires, documentation, and literature reviews. The findings indicate that: (1) the work environment positively and significantly affects work productivity; (2) the organizational climate also has a positive and significant impact on work productivity; and (3) motivation contributes positively and significantly to work productivity. Overall, work productivity is significantly influenced by the work environment, organizational climate, and motivation, with organizational climate exerting a greater influence than the other two factors. Together, these three elements account for 97.00% of the variance in work productivity, while the remaining 3.00% is attributed to external factors such as enthusiasm, ability, and discipline.